Paralympic VR: an immersive experience - Delmazo, Caroline (2018)
Paralympic VR: an immersive experience is based on exploratory research and consists in the production of a 360 video-prototype that aims to give special access to the wheelchair basketball training universe, bringing the users close to Paralympic athletes without the need to hide the impairment or hyper focus on the stories behind the disability. Media coverage of Paralympic sports and the representation of disabled athletes have been changing, but still present a medicalised framing, a narrative where the athletes are commonly portrayed as heroes due to the overcoming of difficulties related to the impairment and not to the sports results. This present project work considers immersive journalism and the use of virtual reality technologies as the means by which an alternative approach and a better representation of Paralympians are possible. The project presents the description of the workflow process, detailing conceptualization decisions, technical aspects and, mainly, the challenges and lessons learned. A user study combining focus groups and online survey was also conducted in order to have insights about the experience of watching the video with the headset Samsung Gear VR. Feedback provided by participants indicated that the prototype accomplished its aim. Recommendations to improve future work were also gathered.